2015
DOI: 10.2105/ajph.2015.302699
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Mental Health Referral and Diagnosis in the New York City Jail Mental Health Service

Abstract: Objectives. To better understand jail mental health services entry, we analyzed diagnosis timing relative to solitary confinement, nature of diagnosis, age, and race/ethnicity. Methods. We analyzed 2011 to 2013 medical records on 45 189 New York City jail first-time admissions. Results. Of this cohort, 21.2% were aged 21 years or younger, 46.0% were Hispanic, 40.6% were non-Hispanic Black, 8.8% were non-Hispanic White, and 3.9% experienced solitary confinement. Overall, 14.8% received a mental health diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 13 publications
2
29
0
Order By: Relevance
“…These challenges may, if unmet, increase older former inmates’ risk for repeat arrest and future incarceration. Recent research about prisoners with PTSD has found that they are 43% more likely to be rearrested in the same year compared to those without PTSD (Kaba et al, 2015), further underscoring our finding that older jail inmates with symptoms of PTSD should be considered a high-risk population in need of enhanced medical and social services. As such, coordination of correctional and community health services for this population prior to reentry could be important for improving access to care, adherence to mental and other health treatment plans, and reducing health disparities and recidivism (Binswanger, Redmond, Steiner, & Hicks, 2012).…”
Section: Discussionsupporting
confidence: 76%
“…These challenges may, if unmet, increase older former inmates’ risk for repeat arrest and future incarceration. Recent research about prisoners with PTSD has found that they are 43% more likely to be rearrested in the same year compared to those without PTSD (Kaba et al, 2015), further underscoring our finding that older jail inmates with symptoms of PTSD should be considered a high-risk population in need of enhanced medical and social services. As such, coordination of correctional and community health services for this population prior to reentry could be important for improving access to care, adherence to mental and other health treatment plans, and reducing health disparities and recidivism (Binswanger, Redmond, Steiner, & Hicks, 2012).…”
Section: Discussionsupporting
confidence: 76%
“…The type and severity of disorder diagnosed by a psychiatric expert witness usually plays an essential role when considering high-security hospital treatment for mentally ill offenders (27-29, 31, 43, 48). Research suggests that ethnic-minority patients are susceptible to stereotyping by physicians, psychiatrists, and judges, which implies that the complexity of their psychiatric assessment might be reduced to prejudiced assumptions about patient adherence to treatment recommendations and to associating signs of mental illness with personality traits rather than actual health disorders (19,27,43,(62)(63)(64)(65). In a UK study, Mikton and Grounds (63) searched for disparities in the diagnosing of personality disorders by forensic psychiatrists working with different ethnic groups in England and Wales.…”
Section: Discussionmentioning
confidence: 99%
“…The rising percentages of foreign nationals in the penal system has raised questions about their health conditions. Multiple sources indicate serious mental health issues among ethnic-minority and immigrant prisoners (15)(16)(17)(18)(19)(20)(21)(22)(23). Recent research suggests that the majority of factors leading to mental health vulnerability among prisoners, such as language barriers, isolation, cultural misunderstanding, and legal standing, are even more salient for foreign national prisoners (4,12,13,(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cross-sectional studies undertaken on community dwelling samples, PTSD has been consistently found to be associated with grater rates of self-reported contacts with the criminal justice system (Collins & Bailey, 1990;Donley et al, 2012). More recent research on released prisoners with PTSD showed that a majority of those justice-involved persons with PTSD were more likely to be rearrested within the same year for a new felony charge relative to prisoners without PTSD (Kaba et al, 2015;Peller, Najavits, Nelson, LaBrie, & Shaffer, 2010;Sadeh & McNiel, 2015), indicating that jail inmates with severe PSTD symptoms should be conceived as high risk population requiring more attention.…”
Section: Original Articlementioning
confidence: 99%